A convergence between cultural heritage and shipbuilding science - Mazarakos, Thomas; Vasileios Vasileiadis; Dimitrios Lyridis; Ekaterini Delegou; Sarantidis, Sarantos; Antonia Moropoulou (Technical Annals, 2024)
In the contemporary context, the demand for wooden vessels remains prevalent in the domains of fisheries, tourism and contemporary sailing. This necessitates a convergence of traditional shipbuilding techniques and contemporary naval engi-neering. In this regard, there is a growing imperative for the scientific documenta-tion of traditional shipbuilding practices, utilising modern techniques such as three-dimensional documentation and representation. Concurrently, contemporary naval engineering contributes to the design of lines plan. This advanced docu-mentation facilitates the estimation of hydrodynamic resistance through the utili-sation of modern calculation methodologies. The integration of contemporary na-val engineering, material science and engineering optimisation of materials’ inter-ventions and maintenance with traditional shipbuilding art in an arsenal has mod-ernised, reproduced and made viable the construction of a traditional boat. Inno-vative practices must be adopted to ensure the revival of the arsenals and the fu-sion of traditional shipbuilding and naval engineering, leading to the wooden ships that Aegean, Mediterranean and the world need. The aim of this paper is to present a comprehensive action plan for the cultural, digital and scientific docu-mentation of traditional wooden shipbuilding art. The complete, comprehensive and multidimensional documentation constitutes the basic foundation of the sus-tainable development and promotion of the Greek shipbuilding tradition. The proposed plan is not confined to the collection, recording and study of the tradi-tional vessels currently being preserved; rather, it employs a comprehensive and multifaceted approach, with targeted actions, seeking the recognition of traditional shipbuilding as an integral part of the cultural heritage and its preservation and transmission to future generations.